OPTIMALISASI PEMANFAATAN SUMBERDAYA AIR MELALUI PERBAIKAN POLA TANAM DAN PERBAIKAN TEKNIK BUDIDAYA PADA SISTEM USAHATANI - Hasmari Noer (Indonesian Journal of Agricultural Economics, 2011)
Agricultural sector is the main water user, so it is important to manage water use toimprove its utilization and efficiency. In utilizing water resources there are a lot ofperceived problems among users of water. Based on many previous studies, some possibleefforts to optimize water utilization are by improving the cropping pattern and cultivationtechniques. Regarding this matter, the first aspect to note is the characteristic of the region.For the agricultural sector, regional characteristics and rainfall pattern are importantreferences to be considered in setting up water management strategy so the use of watereither from rain or irrigation causes no damage to the environment and can provide optimalresults. This strategy can be applied in determining the type of commodity, time of plantingand cropping patterns related to rainfall patterns to avoid harvest failure. Rotation ofcommodities and use of mulch are also some strategies to use water optimally andefficiently. Rotation of commodities is well-developed among farmers. The use of strawmulch to improve the soil has also been developed in cropping systems on rice-palawijafarming.Key words: water resources, utilization, optimalization, efficiency